Mineralização e formação de gases da degradação de Eichhornia azurea Kunth e Egeria najas Planch - Bitar, Alexandre Luccas (Universidade Federal de São Carlos, 2003)
The decomposition of macrophytes may constitute in an important source of carbon for the functioning of aquatic ecosystems. The experiments developed in this study aimed to describe mineralization aspects such as kinetics and formation of CO2 and CH4 from the anaerobic decomposition of the aquatic macrophytes Eichhornia azurea Kunth and Egeria najas Planch. Samples of these plants and of water were collected in the Óleo lagoon (Ecological Station of Jataí, Luiz Antônio district SP; 21o33 - 21o37 S, 47o45 - 47o52 W). In the laboratory two experiments were conducted: the first aimed to describe the kinetics of carbon transformation through the quantification of the reminiscent fractions; the second aimed to describe the variations of the gas products (CO2 and CH4). Fragments of E. azurea and E. najas, along with water samples from the lagoon, were added to decomposition chambers in the proportion of 8 g L-1 (PS). The CO2 and CH4 emissions were determined through chromatography. The results of E. azurea showed that, on the first phase of mineralization, the mass losses varied between 24,91 and 23,93%, with decay coefficients of 0,55 and 1,5 day-1. For E. najas the mass losses varied between 25 and 67%, depending on temperature. The decay coefficients were of 0,14 and 0,17 day-1 (E. najas). The production of CO2 for both species was, overall, higher when temperatures were 17,7 and 20,3 oC. The production of methane was favored at 22,4 and 27,0 oC. The results allowed to infer that, at the Óleo lagoon, the conversion of the label debris fraction of Egeria najas is favored at higher temperatures and its mineralization coefficient are relatively low. The rate of mineralization of refractory carbon of Egeria najas, in this lagoon, is probably increased with temperature elevation.
Keywords: Limnologia; Macrófitas aquáticas; Metano; Modelos cinéticos; Egeria najas; Eichhornia azurea; CIENCIAS BIOLOGICAS